From fields to fortune: An inspiring journey of a millet farmer to successful entrepreneur - Chapke, Rajendra R.; Srinivas, A.; Anuradha, N.; Swarna, R.; Priyanka, V. (Indian Farming, 2025)
Being an entrepreneur is a difficult decision that requires courage to overcome obstacles, an incredible amount of patience and enough risk taking capacity. The story of a farmer who became an entrepreneur, and now a well-known businessman is narrated to encourage other millet farmers. His story tells us about how successfully he integrated millets production with processing, valueaddition in a business mode under Farmer FIRST Programme (FFP). He is a beacon of success in the millets sector. His journey, marked by passion and innovation, highlights the impact of adopting modern agricultural practices and adding value to traditional crops with marginal resource status.